Education crisis for Iraqi children - J R A Williams (Forced Migration Review, 2007)
Displaced Iraqi children – both those inside Iraq and in neighbouring states – are being denied their right to education. It is vital to gather accurate data on displaced children and to engage children and adults in displaced communities in pragmatic ways to provide education despite the current circumstances.